Social rights in the technological era. Particular reference to the right to protection of health - León-Alonso, Marta (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The author seeks to overcome the division between freedom rights and social rights by introducing some variables that play in favor of the latter whenever there are principles such as the need and proportionality. Amid the recent crisis, it is a sobering article that invites us to rethink the economic, social and cultural rights.